Mapping the restoration of degraded peatland as a research area: A scientometric review - Apori, Samuel Obeng; Mcmillan, Douglas; Giltrap, Michelle; Tian, Furong (Frontiers in Environmental Science, 2022)
Degraded peatland reduced many ecosystem services such as water quality and quantity, biodiversity, carbon storage, climate regulations and other cultural benefits. Therefore, several initiatives for the restoration of degraded peatland (RDP) have been attempted to restore the ecosystem processes, productivity and services of the degraded peatland to its original natural condition. Notwithstanding the popularity of RDP research among researchers and industry practitioners, a quantitative technique to map a comprehensive survey of the intellectual core and the general body landscape of knowledge on RDP research does not exist. In this study, a scientometric analysis was employed to analyze 522 documents using VOSviewer and CiteSpace. The Web of Science database was used to retrieve bibliographic records using the advanced search “TS (topic) =(‘drained peatland restoration’ OR ‘drained bog restoration’ OR ‘drained mire restoration’ OR degraded peatland restoration’ OR ‘degraded bog restoration’ OR ‘drained peatland reclamation’ OR ‘drained bog restoration’ OR ‘degraded peatland reclamation’ OR ‘degraded bog reclamation’ OR ‘drained mire restoration’ OR ‘degraded mire reclamation’ OR ‘degraded fen restoration’ OR ‘drained fen reclamation’). The outcome sought to provide relevant information in RDP research such as (i) publication trend (ii) research outlet (iii) most influential keywords (iv) most influential institutions and authors (v) top influential countries active in RDP research. In addition, four clusters were identified for ascertaining the central theme of RDP research in which cluster one is linked to the central research theme-“impact of drainage on peatland ecosystem services; cluster two focused on the impact of peatland restoration on greenhouse gas emissions; cluster three is associated with peatland restoration and biogeochemical properties and cluster four is related to peatland restoration and species richness. A new research hotspot such as soil respiration was identified via the keywords with the strongest citation bursts. This study will provide the various stakeholders such as industry, journal editors, policymakers and researchers instinctive understanding of the research status and the development frontier of RDP research.